Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
We have the following equations:
First equation
[tex]x-y=3[/tex]Second equation
[tex]\frac{1}{2}x+y=3[/tex]The first thing we will do is clear the first equation:
[tex]\begin{gathered} x-y=3 \\ x=3+y \end{gathered}[/tex]The second thing we will do is replace the found value of "x" in terms of "y", in the second equation and solve for "y"
[tex]\begin{gathered} \frac{1}{2}x+y=3 \\ \frac{1}{2}(3+y)+y=3 \\ \frac{3}{2}+\frac{y}{2}+y=3 \\ \frac{3}{2}y=3-\frac{3}{2} \\ \frac{3}{2}y=\frac{3}{2} \\ y=\frac{3}{2}\cdot\frac{2}{3} \\ y=1 \end{gathered}[/tex]In conclusion, the value of "y" is 1
The third thing we will do is to replace the found value of "y" in the first equation
[tex]\begin{gathered} x=3+1 \\ x=4 \end{gathered}[/tex]In conclusion, the solution to this system of equations is:
[tex]\begin{gathered} y=1 \\ x=4 \\ (4,1) \end{gathered}[/tex]Therefore, (6,3) is not the solution to this system of equations.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.